Różnorodność kulturowa i jej implikacje względem postaw rodziców wobec trudności w uczeniu się ich dzieci – przyczynek do badań - Gonen-Avital, Shiri (Studia Edukacyjne, 2020)
Background: Israel is a land of immigration – a multicultural society with a mosaic of different cultures. There are four maim ethnic groups in Israel: "Sabre" (born in Israel), Arabs, Russian, and Ethiopian. The main aim of this article is to present the connection between two main issues: Culture Diversity and the Attitudes of Israeli parents to children with Learning Disability (LD). This article stems from a deep and extensive dissertation research on parents' attitudes toward their child Learning Disability in Israel and it is an outline of the research study. Family: The resilience and strength of the family depend on the social, cultural and personality of the family in general, and parents in particular. The parents play a crucial role in facilitating and maintaining wellness in children with developmental disorders. Learning Disability: Today, in the modern world, in the information era, when processing information skills are necessary in everyday life, Learning Disability turn into a widespread phenomenon. Learning disability is a general term that refers to a heterogeneous group of disorders manifested in the acquisition and operation of attention, speaking, reading, writing, or mathematical abilities. Within the Hebrew students in Israel (years 2013-2014), 10.10% are diagnosed with learning disability. In summary, due to the fact that Israel is an immigration country, it is vital to research the implication of parents' attitudes toward their child Learning Disability for the wellbeing of the family and the society.